BIDAN ATAU DUKUN? PILIHAN IBU HAMIL DALAM PERTOLONGAN MELAHIRKAN (Studi Pada Ibu Hamil di Wilayah Kerja Puskesmas Sulamadaha, Kota Ternate) - Ramli *; Nindi Habari (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2020)
In people who have strong culture and traditions, in their daily activities they tend to use a traditional approach in solving their problems. Traditional healers always give birth assistance for pregnant women in traditional societies. On the other hand, to maintain the safety of mothers and babies, government policy requires that birth assistance must be provided by a midwife or medical personnel. Referring to this phenomenon, the focus of the study is the choice of pregnant women in childbirth assistance, between midwives or traditional birth attendants. The method used is qualitative, with an ethnometodological approach, with technical domain data analysis. The results showed that pregnant women prefer midwives in providing delivery assistance, because they are considered safer from a medical perspective. In addition, the motivation given by midwives, traditional healers and community leaders is very important for pregnant women in determining the bonding aid personnel.